INFLUENCE OF MYCOTOXINS ON IMMUNE RESPONSES AGAINST SALMONELLA TYPHIMURIUM INFECTION OF BROILER CHICKENS - & ALwan, Jawad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Forty broiler chickens, One - day old were randomly divided into four equal groups: 1st group was immunized with 0.5 ml of whole sonicated salmonella antigens (WSSAgs), protein concentration 1.89 mg/ml. Two dose two weeks intervals, S/C at 7 days old and the chicks fed contaminated diet with mycotoxins for 7 week, 2nd group was immunized with WSSAgs only and treated as 1st group, 3rd group fed diet contaminated with mycotoxins and 4th group was fed normal diets and served as control negative group, At 30 days, skin test, phagocytic index and serum levels of antibody titers were done, then 1st ,2nd and 3rd groups were inoculated with high dose of virulent S.typhimurium , (1ml containing 1 10 12 CFU/ml ), I/V, and 4th group was inoculated I/V,1ml sterile normal saline and served as control negative group , all chicks were sacrificed at 3 weeks post infection, it was recorded that mycotoxin suppress the cellular and humoral immune responses , phagocytic activity ,in addition to high mortality rate were found in chicks fed contaminated diet with and without immunization.